DEVELOPMENT OF AESTHETIC FEELINGS OF FUTURE TEACHERS TECHNOLOGIES - Yu.O. Kruhla (Academy of Cognitive and Natural Sciences, 2008)
In this article і analyse the importance of developing of esthetic feelings. The meaning of developing of esthetic feeling for the social activity of future teacher is opening.